THE REGULATORY T-LYMPHOCYTES IMMUNOSUPPRESSOR EFFECTS OF BLOOD UNDER DISSEMINATED PULMONARY TUBERCULOSIS WITH MULTI-DRUG RESISTANT M. TUBERCULOSIS - Ye. G. Churina; O. I. Urazova; V. V. Novitsky; T. Ye. Kononova (Бюллетень сибирской медицины)
The work analyzed subpopulation structure of peripheral blood T-regulatory cells (T-reg) and production of cytokines with immunosuppressor activity (IL-10, TGF-b) in vitro in patients with disseminated pulmonary tuberculosis, depending on the sensitivity of Mycobacterium tuberculosis to anti-tuberculosis drugs. It has been shown that Trn – natural T-regulatory lymphocytes (CD4+CD25+Foxр3+) and TGF-b cytokine, formed by them, play the leading role in the formation of immunosuppression under disseminated pulmonary tuberculosis. Besides, subpopulation imbalance of Treg-cells in patients with disseminated pulmonary tuberculosis, in case at multi-drug-resistance and drug-susceptible, is shown by the increased content of T-reg-cells with CD4+CD25+Foxр3+phenotypein combination with the deficiency of CD4+CD25+Foxр3– T-reg lymphocytes in blood. The increase in the amount of CD4+CD25+Foxр3+ T-reg-cells in blood of patients with disseminated multi-drug resistance pulmonary tuberculosis is associated with the increase in basal and BCG-induced production of TGF-bin vitro.